Investigating the adjacent patient radiation dose received during a simulated ward chest X-ray examination - Hayley Langfield; Paul Lockwood (Radiography Open, 2023)
Introduction: A patient having a chest X-ray will inevitably be exposed to radiation from the primary beam. Using a light beam diaphragm (LBD) on the X-ray tube reduces scattered radiation at the X-ray tube through longitudinal and horizontal collimation. But not scattered secondary radiation resulting from interactions of the primary beam. This study aimed to investigate whether lead protection on simulated hospital ward inpatients (opposite and adjacent to a simulated chest X-ray examination) would change the secondary scattered radiation dose received.